Augmented and virtual reality : second International Conference, AVR 2015, Lecce, Italy, August 31-September 3, 2015, Proceedings /: second International Conference, AVR 2015, Lecce, Italy, August 31-September 3, 2015, Proceedings. (2015) - Unknown
No abstract available